Pengelolaan Pembelajaran Bahasa Indonesia Berkarakter, Aktif, Dan Menyenangkan Di Kelas III SD Muhammadiyah Program Khusus Kottabarat Surakarta - RAHMAWATI, Fitri Puji; , Prof. Dr.Sutama, M.Pd (2015)
The purpose of this study consists of three goals. These objectives, namely: describing material management, interaction management, and management of learning evaluation Indonesian character, active, and fun. This qualitative research design using phenomenology. Location of the study conducted in SD Muhammadiyah Surakarta Special Programme Kottabarat. Informants consisted of principals, teachers, and students. Data collection techniques using direct observation passive role, open questionnaire, interview, and documentation. Data analysis technique is done through four stages which include data collection, data reduction, data presentation, and conclusion/verification. Apply data validation and method triangulation. Research results that have been achieved three things. 1) Management of Indonesian material carried by utilizing a variety of learning methods. The ability to listen through hearing experience peers, talk to share the experience or traveling, reading through the reading of poetry and drama texts, and write method writes poetry and plays. 2) Learning interaction between teachers and learners or learning interaction in many directions. The interaction between all students can build with the four language skills, as well as teacher-student interaction so that learning becomes active and fun. 3) Evaluation of learning Indonesian in cognitive done before and ending with the use of a written test and a description in the form of learning objectives. Affective and psychomotor evaluation performed during the learning process is to look at the attitude of learners during the learning process.